Demonstration of high Johnson’s figure of merit (ft × VBR >20 THz·V) and fmax × VBR (>42 THz·V) for Al0.66Ga0.34N channel MISHEMT on bulk AlN substrates - Ruixin Bai; Swarnav Mukhopadhyay; Khush Gohel; Surjava Sanyal; Jiahao Chen; MD Tahmidul Alam; Shuwen Xie; Shubhra S. Pasayat; Chirag Gupta (Applied Physics Express)
In this paper, a metal-organic chemical vapor deposition (MOCVD) grown Al _0.66 Ga _0.34 N channel metal-insulator-semiconductor-high-electron-mobility-transistor (MISHEMT) with a scaled T-gate structure was fabricated on a single-crystal bulk AlN substrate. A device with 4 μm source-to-drain spacing achieved a record-high Johnson’s figure of merit (JFOM) of 20.92 THz·V, enabled by the high-Al channel, high-quality substrate, and gate field-plate. The corresponding cutoff and maximum oscillation frequencies are 22.5 GHz and 46 GHz, respectively, with a breakdown voltage of 930 V. A current collapse of 15% was observed under 30 V drain bias, indicating excellent radio-frequency (RF) performance and the potential of bulk-AlN-based AlGaN channel high-electron-mobility-transistors (HEMTs) for advanced RF applications.